Meta-Analysis: Application of Health Belief Model on the Adherence to Antihypertensive Medication - Eltigeka Devi Apriliani; Hanung Prasetya; Bhisma Murti (Journal of Health Promotion and Behavior, 2022)
Background: Non-adherence to treatment and lack of understanding of the use of antihypertensive drugs resulted in uncontrolled hypertension. Antihypertensive compliance as a top priority in the treatment of hypertensive patients through the implementation of the Health Belief Model. The purpose of this study was to analyze the effect of perceived benefits and received cues to act on antihypertensive medication adherence.Subjects and Method: This meta-analysis was conducted using the PRISMA flowchart guideline. The study was conducted using the PICO model, Population: hypertensive patients, Intervention: perceived benefits were strong and received cues to act, Comparison: perceived benefits were weak and did not receive cues to act, Outcome: adherence to antihypertensive medication. The article search process was carried out between 2012 and 2022 using databases from Pub¬Med, Google Scholar, ScienceDirect and ProQuest. Search keywords included “health belief model” OR “perceived benefit” OR “cues to action” AND “adherence antihypertensive” OR “compliance antihypertensive” AND “hypertension” OR “high blood pressure”. Based on the database, there were 13 articles that met the inclusion criteria. Research analysis was carried out using RevMan 5.3 software.Results: There are 13 articles from the continents of Africa and Asia. There are 9 meta-analysis articles showing that a strong perceived benefit of hypertension treatment is 1.60 times more likely to adhere to antihypertensive treatment than a weak perception of benefit and is statistically significant (aOR = 1.60; 95% CI = 1.06 to 2.41; p = 0.020), and there were 8 articles discussing the effect of getting cues to act on hypertension treatment on 1.52 times more likely to adhere to antihypertensive medication than not getting cues to act and statistically significant (aOR = 1.52; 95% CI = 1.02 to 2.27; p = 0.040).Conclusion: Strong and signaled benefit perception for hypertensive patients improves adherence to antihypertensive medication.Keywords: hypertension, health belief model, perceived benefits, cues to action.Correspondence:Eltigeka Devi Apriliani, Masters Program in Public Health, universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: eltigeka13@gmail.com. Mobile: +62 85735387363.Journal of Health Promotion and Behavior (2022), 07(03): 238-249DOI: https://doi.org/10.26911/thejhpb.2022.07.03.06